Geopoetic Satire in Will Self’s Walking to Hollywood: Re-writing the Borders of Modernity - Myrto Petsota (Études Britanniques Contemporaines, 2025)
Walking to Hollywood’s obsessive and delirious narrator allows Will Self to achieve an astonishing success: reconciling a self-irony as merciless as his social satire. Ultimately, the novel invites readers to question the limits of satire and explore alternative cultural spaces beyond the text’s confines. This paper examines the geopoetic and satirical dimensions of Self’s novel, focusing on its critique of Western modernity. Through an analysis of the protagonist’s physical and psychological journeys—from the eroding coastline of Holderness to the surreal landscapes of Los Angeles—the paper demonstrates how Self transforms symptoms of mental disintegration into literary tropes, recasting ‘pathology’ as civilisational illness. By examining the crossing of geographical, mental, and cultural borders, the paper reveals how Self’s ‘intellectual nomadism’ seeks an escape from the perceived cultural deadlock of the West, ultimately crafting a new topology of existence.